121 ADENOCARCINOMA OF THE LUNG PRESENTING AS DEEP VENOUS THROMBOSIS AND PULMONARY EMBOLISM. (1st January 2006) - Lokhandwala, N.; Godkar, D.; Patel, A.; Yakoby, M.; Niranjan, S.
Abstract : Case Report: A 55-year-old patient was admitted with pain and swelling of his left leg for 2 weeks. He also complained of mild shortness of breath at rest for 1 week with progressive worsening on exertion. He was a heavy smoker (80 pack-years) but otherwise has no significant medical history. He had not seen a doctor for 30 years. On examination he had calf asymmetry with redness and tenderness of left calf. Venous Doppler of the left leg showed acute deep venous thrombosis in left popliteal vein. In view of shortness of breath and chest x-ray finding of right-sided hazy opacity, pulmonary embolism with possible pulmonary infarction was suspected. Computerized tomography (CT) of the chest with intravenous contrast confirmed filling defects in proximal branches of left pulmonary artery consistent with pulmonary embolism but also showed a right lung supra hilar mass, bilateral mediastinal lymphadenopathy, and multiple low attenuation foci in the liver suggestive of liver metastases. In view of the above findings the patient had CT-guided biopsy of liver lesions, which were confirmed as mucinous adenocarcinoma on microscopy. Subsequent work-up in the hospital also showed metastases to bone and brain. In view of the above findings the patient was offered palliative chemotherapy and radiotherapy but refused any treatment. Discussion: Presentation of carcinoma of lung with deep venous thrombosis is rare although the risk of venous thrombosis in lung cancer patient is increased 20-fold compared to the general population. Patients with adenocarcinoma have a higher risk of developing deep venous thrombosis as compared to patients with squamous cell carcinoma.